Hematology and coagulation a comprehensive review for board preparation, certification, and clinical practice - Wahed, Amer; Dasgupta, Amitava 1958- (Elsevier, 2015)
This basic primer offers practical examples of how things function in the hematopathology clinic as well as useful lists, sample questions, and a bullet-point format ideal for quick pre-board review. This book provides only the most clinically relevant examples designed to educate senior medical students, residents and fellows and "refresh" the knowledge base, without overwhelming students, residents, and clinicians